Genetic Architecture of Resistance to Alternaria brassicae in Arabidopsis thaliana: QTL Mapping Reveals Two Major Resistance-Conferring Loci - Rajarammohan, Sivasubramanian; Kumar, Amarendra; Gupta, Vibha; Pental, Deepak; Pradhan, Akshay K.; Kaur, Jagreet (Frontiers in Plant Science, 2017)
Alternaria brassicae, a necrotrophic fungal pathogen, causes Alternaria blight, one of the most important diseases of oleiferous Brassica crops. The current study utilized Arabidopsis as a model to decipher the genetic architecture of defense against A. brassicae. Significant phenotypic variation that was largely genetically determined was observed among Arabidopsis accessions in response to pathogen challenge. Three biparental mapping populations were developed from three resistant accessions viz. CIBC-5, Ei-2, and Cvi-0 and two susceptible accessions - Gre-0 and Zdr-1 (commonly crossed to CIBC-5 and Ei-2). A total of six QTLs governing resistance to A. brassicae were identified, five of which were population-specific while one QTL was common between all the three mapping populations. Interestingly, the common QTL had varying phenotypic contributions in different populations, which can be attributed to the genetic background of the parental accessions. The presence of both common and population-specific QTLs indicate that resistance to A. brassicae is quantitative, and that different genes may mediate resistance to the pathogen in different accessions. Two of the QTLs had moderate-to-large effects, one of which explained nearly 50% of the variation. The large effect QTLs may therefore contain genes that could play a significant role in conferring resistance even in heterologous hosts.